ผลของกลุ่มพัฒนาตนต่อสุขภาวะทางจิตของผู้สูงอายุ - วรัปสร โรหิตะบุตร (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
To investigate the effect of personal growth group on psychological well-being of the elderly, through quantitative and qualitative data. The quantitative data was obtained through the quasi-experimental research with the randomized pretest-posttest control group design. Participants were 19 elderly in Baan Banglamung Home for the Elderly, who scored below the mean on the Psychoogical Well-being Scale, with 9 persons in the experimental group and 10 persons in the control group. The experimental group participated in a Trotzer s personal growth group program conducted by the researcher, for a session of one to and a half hours, 3 to 5 sessions a week, over a period of 3 consecutive weeks for the total of 12 session, which made approximately 18 hours. The instruments used was the Psychological Well-being Scale. Data was analyzed using the t-test and one-way ANOVA repeated measures followed by post hoc comparisons with LSD test. The major findings were as follows 1) The posttest and the follow-up scores on psychological well-being of the experimental group were higher than its pretest scores at .001 level of significance. No differences on those scores were found between the posttest and the follow-up data. 2) The posttest scores on psychological well-being of the experimental group were higher than those of the control group at .05 level of significance. The qualitative data was obtained through indepth interview with 9 participants of the experimental group, from the quantitative part, during the follow-up period. The content analysis of the data indicated that the elderly perceived the beneficial effects of the personal growth group. Experiances during the group process which facilitating, promoting and sustaining the psychological well-being of the elderly were 1) the positive interactions and warm and trusting relationships between the leader and the members and among the members in the group which facilitating self-exploration, self-disclosure and personal sharing among the members 2) the supportive and meaningful relationships experienced by the elderly which facilitating their understanding and acceptance of themselves, others, and their issues and promoting their positive changes and growth.